Effect of nitrogen fefitilization or legumes on liveweight gain of steers grazing guinea grass pastures - Favoretto, Vanildo; Reis, Ricardo Andrade; Vieira, Paulo de Figueiredo; Malheiros, Euclides Braga (Pesquisa Agropecuaria Brasileira, 2014)
The purpose of this trial was to evaluate the liveweight gam of steers grazing three types of Guinea grass pastures: grass alone (control), grass with nitrogen fertilization (100 kg/ha) and grass-legume mixture of perennial soybean (Neonoronia wightii Verdc) and centrosema Centrosema pubescens Benth). Twelve to fifteen-month old Guzerá male steers with 210kg of mean liveweight were used. The pasture-animal adjustment was realized by put-and-take method in a rotational grazing system. Animals were weighed and pasture samples were collected at 35 day intervals. During dry season, the daily and per hectare liveweight gain in the grass-legume mixture (0.264 kg/head/day and 85.73 kg/ha) were greater than the nitrogen fertilized (0.114 kg/head/day and 19.93 kg/ha) and the control (0.140 kg/head/day and 36.60 kg/ha). In a 15-month period nitrogen fertilized and grass-legume pastures showed no difference between liveweight gain per hectare, however these treatments were 16% upper when compared with the control.